Peluang Dan Ancaman Hubungan Perdagangan Indonesia - Thailand Komoditas Pertanian Pada Produk Gula - Putri mustikasari; Della Safitri; Arini Eka Saputri; Ahmad Madani; Daspar (CV. ITTC INDONESIA, 2024)
This research analyzes trade relations between Indonesia and Thailand in sugar products, with a focus on agricultural commodities. International trade data is used to display trade The method in this research uses descriptive analytical research methods while the data source taken in this research is secondary data. The results show that sugar trade relations between Indonesia and Thailand are influenced by factors such as trade policy, international prices, domestic production, and consumer demand. Policy implications are designed toincrease trade cooperation and strengthen the position of the two countries in the globalsugar market.Thailand is the largest sugar producing country in the world with high quality and sets pricesto reach the general public, because the price of sugar produced in Indonesia is set at a highprice making it difficult to reach while the amount of domestic demand continues to increaseevery year